Somapower: Somaesthetics Reads Politics - Koczanowicz, Leszek, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2024)
We do politics in, through, and as bodies. All our political activity is inevitably corporeal. Parliamentary debates, party assemblies, street demonstrations, and civil disobedience are all bodily actions. Political regimes maintain their power by controlling our bodies, both through explicit acts of violence and, more insidiously, by inculcating somatic norms of obedience to the political authorities and ideologies. This oppression can be effectively challenged if we use somaesthetics to identify and examine the bodily habits and feelings that express and reinforce such domination. Somaesthetically explored, they can be refashioned and help overcome the oppressive social conditions that produce them.